2019
DOI: 10.1097/ta.0000000000002427
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia/reoxygenation decreases endothelial glycocalyx via reactive oxygen species and calcium signaling in a cellular model for shock

Abstract: BACKGROUND Ischemia/reperfusion injury (IRI) has been shown to cause endothelial glycocalyx (EG) damage. Whether the hypoxic/ischemic insult or the oxidative and inflammatory stress of reperfusion plays a greater part in glycocalyx damage is not known. Furthermore, the mechanisms by which IRI causes EG damage have not been fully elucidated. The aims of this study were to determine if hypoxia alone or hypoxia/reoxygenation (H/R) caused greater damage to the glycocalyx, and if this damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…In fact, calcium content correlated positively with cardiac dysfunction and mitochondrial damage, which could be expected, as hyperkalemic cardioplegia can potentially exacerbate Ca 2+ overload and increase reperfusion injury 14 . In addition, calcium content correlated positively with glycocalyx degradation, which is in agreement with Jackson-Weaver et al, 37 who observed that I/R injury promoted Ca 2+ release from endothelial cells, which led to glycocalyx damage in cultured cells.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, calcium content correlated positively with cardiac dysfunction and mitochondrial damage, which could be expected, as hyperkalemic cardioplegia can potentially exacerbate Ca 2+ overload and increase reperfusion injury 14 . In addition, calcium content correlated positively with glycocalyx degradation, which is in agreement with Jackson-Weaver et al, 37 who observed that I/R injury promoted Ca 2+ release from endothelial cells, which led to glycocalyx damage in cultured cells.…”
Section: Discussionsupporting
confidence: 90%
“…These oxygen free radicals go on to promote hypoxia-inducible transcription factor expression that may sustain pro-inflammatory cytokine production and signaling [57] . Together, the higher presence of reactive oxygen species and circulating pro-inflammatory milieu [58] during chronic hypoxemia increase the risk of EG thinning [59] , though the impact of chronic hypoxemia on pediatric EG expression has not been systematically evaluated.…”
Section: Influence Of Comorbiditiesmentioning
confidence: 99%
“…Children who require CPB generally have a congenital heart defect requiring corrective or palliative surgical intervention or need heart and/or lung transplantation. Depending on the type of congenital heart defect or degree of lung disease requiring transplantation, some children live with chronic hypoxia prior to palliative surgery that, as discussed above, can promote pro-inflammatory endothelial cell signaling [201] and endothelial surface layer thinning [59] . Then, with transition to CPB at the time of surgical intervention, regions of the body experience variable states of hypoperfusion and ischemia.…”
Section: Extracorporeal Life Supportmentioning
confidence: 99%
“…Glycocalyx disruption results in organ impairment and loss in critically ill patients (Table 2). [ 31 ]…”
Section: The Egx In the Pathophysiologymentioning
confidence: 99%